Epithelial ovarian cancer is infiltrated by activated effector T cells co-expressing CD39, PD-1, TIM-3, CD137 and interacting with cancer cells and myeloid cells - Tassi, Elena; Bergamini, Alice; Wignall, Jessica; Sant’Angelo, Miriam; Brunetto, Emanuela; Balestrieri, Chiara; Redegalli, Miriam; Potenza, Alessia; Abbati, Danilo; Manfredi, Francesco; Cangi, Maria Giulia; Magliacane, Gilda; et al. (Frontiers in Immunology, 2023)
Introduction: Despite predicted efficacy, immunotherapy in epithelial ovarian cancer (EOC) has limited clinical benefit and the prognosis of patients remains poor. There is thus a strong need for better identifying local immune dynamics and immune-suppressive pathways limiting T-cell mediated anti-tumor immunity.In this observational study we analyzed by immunohistochemistry, gene expression profiling and flow cytometry the antigenic landscape and immune composition of 48 EOC specimens, with a focus on tumor-infiltrating lymphocytes (TILs).Results: Activated T cells showing features of partial exhaustion with a CD137 + CD39 + PD-1 + TIM-3 + CD45RA -CD62L -CD95 + surface profile were exclusively present in EOC specimens but not in corresponding peripheral blood or ascitic fluid, indicating that the tumor microenvironment might sustain this peculiar phenotype. Interestingly, while neoplastic cells expressed several tumor-associated antigens possibly able to stimulate tumor-specific TILs, macrophages provided both co-stimulatory and inhibitory signals and were more abundant in TILs-enriched specimens harboring the CD137 + CD39 + PD-1 + TIM-3 + CD45RA -CD62L - CD95 + signature.Conclusions: These data demonstrate that EOC is enriched in CD137 + CD39 + PD-1 + TIM-3 + CD45RA -CD62L -CD95 + T lymphocytes, a phenotype possibly modulated by antigen recognition on neoplastic cells and by a combination of inhibitory and co-stimulatory signals largely provided by infiltrating myeloid cells. Furthermore, we have identified immunosuppressive pathways potentially hampering local immunity which might be targeted by immunotherapeutic approaches.